2002
DOI: 10.1046/j.1524-4725.2002.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Gouty Tophi: A Squamous Cell Carcinoma Mimicker?

Abstract: This is the first report of gouty tophus of the periungual region presenting as a hyperkeratotic lesion. Initial clinical diagnosis favored SCC and histologic evidence suggested a possible early SCC. This lesion can be confused with digital squamous cell carcinoma. The presence of pseu- docarcinomatous hyperplasia may complicate accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Four of 5 cases involved lesions on the ear, 2,3 a relatively common site for gout deposition, and only one reported a lesion in an atypical location, the proximal nail fold of a digit. 4 Four of the 5 patients had a known history of gout, although this was not always realized until after identification of gout in the skin specimen, as in our patient's case.…”
Section: Discussionmentioning
confidence: 54%
“…Four of 5 cases involved lesions on the ear, 2,3 a relatively common site for gout deposition, and only one reported a lesion in an atypical location, the proximal nail fold of a digit. 4 Four of the 5 patients had a known history of gout, although this was not always realized until after identification of gout in the skin specimen, as in our patient's case.…”
Section: Discussionmentioning
confidence: 54%
“…The tophi formation usually occurs over a mean period of 10 years [16]. Tophi are present commonly as subcutaneous, sharply circumscribed nodular collection of monosodium urate crystals [17] at periarticular site in and around bursae and in soft tissue overlying tendon and cartilage [18][19][20]. The most common locations are skin overlying joints and helix of the ears.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Dacko et al reported pseudocarcinomatous hyperplasia associated with gout on the finger of an 84‐year‐old man. The patient presented with a hyperkeratotic papule on the lateral proximal nail fold of the left fifth digit with resulting nail dystrophy.…”
Section: Discussionmentioning
confidence: 99%